Competencies of Jordanian Teachers of Grades 1-3 With Dyslexic Students in Light of Some Variables - Beirat, Mohammad A.; Al- Magharbah, Ensherah Salem; Alkhamaiseh, Zaidan (Journal of Ecohumanism, 2024)
The study aimed to reveal the competencies of Jordanian teachers of the first three grades in dealing with students with dyslexia, and its relationship to the variables of teaching experience, undergoing previous training courses in dyslexia, and the grades they teach. The study sample consisted of (86) male and female teachers who were selected randomly in schools affiliated with the Directorate of Education of Wadi Al-Seer District in the capital, Amman. The study followed the descriptive approach. To achieve the study objectives, the researchers developed a scale of competencies for teachers of the first three grades related to students with dyslexia. It consisted of (41) paragraphs distributed over three dimensions: The first dimension: includes the nature and causes of dyslexia. The second dimension: includes the diagnosis and symptoms of dyslexia. The third dimension: includes therapeutic interventions for dyslexia. The researchers verified the validity and reliability of the scale. The results showed that the competencies of Jordanian teachers of the first three grades in dealing with students with dyslexia were average across the scale dimensions as a whole, with the “diagnostic competencies” dimension ranking first, followed by the “nature and causes of dyslexia” dimension in second place, and the “treatment of dyslexia” dimension in last place. The results also indicated that there were statistically significant differences in the competencies of teachers of the first three grades according to the variable of teaching experience, and the differences were in favor of those with experience ranging between (6 years and less than 11 years). As for the variable of grades (first, second, third) taught by primary school teachers, the differences were in favor of teachers of the first grade, followed by the third grade and then the second grade. As for the variable of attending training courses, the differences were in favor of teachers of the first three grades who attended previous training courses in dyslexia. In light of these results, a set of recommendations were presented.